Effects of organophilic-modified attapulgite nanorods on thermal and mechanical behavior of segmented polyurethane elastomers - Wang, Chia-Hao; Shieh, Yeong-Tarng; Guo, Gangjian; Nutt, Steven (Polymer composites, 2010)
The effects of different grafting content of 4,4′‐methlenebis(phenyl isocyanate)‐modified attapulgite (ATT‐MDI) on thermal and mechanical properties of segmented polyurethane (PU) elastomers were investigated. The ATT‐MDI nanorods with different grafting content were prepared by treating ATT with heat and acid followed by grafting with MDI molecules. MDI‐modified ATT were characterized by transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy. TGA analysis revealed that at least 30 wt % of MDI was grafted/adsorbed on the surface of ATT following the modification. Three PU/ATT‐MDI nanocomposites were in situ synthesized using ATT with different grafting contents, and the materials were characterized by TEM, thermal analysis, and mechanical testing. The tensile strength and modulus increased with increasing grafting content of MDI molecules, and the crystallinity of soft and hard segments was increased by ATT‐MDI. POLYM. COMPOS., 31:1890–1898, 2010. © 2010 Society of Plastics Engineers.